Pengaruh Reputasi Perusahaan dan Kinerja Keuangan terhadap Return Saham : Studi pada Saham LQ45 yang Terindeks pada Corporate Image Index Periode 2020-2022 - Galuh Ayu Novitasari; Khairina Nur Izzaty (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to empirically examine the effect of Corporate Reputation, ROA, NPM, and DER on Stock Returns of LQ45 Index companies during the Covid-19 pandemic. The data in this study uses secondary data obtained from financial reports and corporate image index publications. The population in this study were LQ45 Index companies with a total of 270 companies in the 2020-2022 period. The sampling technique used purposive sampling technique resulting in a research sample of 19 companies. The independent variabels analysed include Corporate Reputation with the proxy Corporate Image Index and Financial Performance with the proxies Return On Assets, Net Profit Margin, and Debt to Equity Ratio. The dependent variabel in this study is stock return. The analytical tools used are descriptive statistics, classical assumption test, multiple linear regression, T test, F test, and R2 determination coefficient test. The results showed that corporate reputation has a significant negatif effect on stock returns, while ROA has a significant positive effect. NPM and DER have no effect on stock returns.